CLINIC MANAGEMENT SYSTEM - Nisa Binti Abu Bakar, Khairun; Danu Nurpathama, Muhammad; Binti Muhammad Hariri, Hamizah (Riviera Publishing, 2023)
This study explores the implementation and benefits of a Clinic Management System (CMS) in healthcare settings. It focuses on the objectives of the CMS, including eliminating errors in form writing, establishing standardized processes and data formats, and generating reports for doctor scheduling and patient disease data storage. The study discusses the challenges faced by clinics in traditional manual-based systems, such as errors in form writing, lack of standardized processes, and the absence of robust reporting mechanisms. It highlights the significance of transitioning to a digital platform for minimizing errors in form writing and emphasizes the importance of intelligent form validation and auto-correction features.